Estudo observacional de sinais clínicos e sintomas em pacientes com periodontite apical - Barreto, Thiago Klaue Menna (2015)
Apical periodontitis is an inflamatory process reported by literature in a prevalence that range from 39% to 83%, depending on the sample studied. The inflammatory process represents and infectious focus that may cause systemic manifestations. Many patients can t identify it, and health professionals may have difficulty in realizing an early diagnostic since this process may be silent. Therefore the objectives of this study ware to evaluate clinical signs and the prevalence of asymptomatic apical periodontitis, through a convenience sample. 146 patients with apical periodontitis were selected, and then answered to a questionnaire. After the data was collected, it was found that the prevalence of patients with asymptomatic apical periodontitis was 57.53%. The analysis of logistical regression was used to evaluate the association between the outcome and possible predictors. The variables that presented a value of p≤0, 20 in univariate analysis were selected and in the adjusted model were kept only the ones that presented a value of p≤0,05. Patients without cavities in their teeth have a odds ratio 2.45 times bigger of not mentioning any painful symptomatology (OR: 2.45 IC: 1.08 5.54); patients that related a response to the vertical percussion test have a 86% lesser odds ratio of not perceiving pain in the dental element (OR: 0.14 IC: 0.06 0.33); smoking patients have a chance 3.96 times bigger of not relating any painful symptomatology (OR: 3.96 IC: 1.09 14.38). It can be concluded that a set of evaluations may provide an early diagnostic and a better interpretation from the patient, reducing the prevalence of apical periodontitis